The Advocate. (California : Liberation Publications, 1971)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweewekelijks
Redactie : One Peninsula Place, Buiding 1730, Suite 225, San Mateo, California 94402 ; vanaf (1997) 227 : 1730 South Amphlett, Suite 225, San Mateo, California 94402, P.O. Box 5847 ; vanaf (1984) 410 : 22761 Pacific Coast Highway, Suite 234, Malibu California, P.O. Box 90265 ; vanaf ? : 1800 Highland Ave. Suite 200, Los Angles CA 90028 ; vanaf (1986 448) : 6922 Hollywood Blvd. 10th floor, Los Angeles, CA 90028
Engels
Periodiek